Evaluation of causes of female infertility by hysteron-laparoscopy - Rani, L. Jhansi; Panda, Akankhya; Haripriya, C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
ABSTRACT Background: Infertility is rising in recent times affecting about 60-80 million couples worldwide. Female infertility can occur due to variety of causes, ranging from hormonal imbalance to congenital anomalies or infections or other pathologies involving uterus, fallopian tubes, ovaries, external genitalia or even error of coitus. Hystero laparoscopy with chromo perturbation is the gold standard diagnostic method in evaluation of tubal factors, uterine and peritoneal disorders. Aims and objectives were to evaluate the different causes of primary and secondary infertility in women of reproductive age using hysteron laparoscopy with chromo perturbation. Methods: It is a prospective observational study done on 50 infertile women. Study population is divided into two groups- primary infertility and secondary infertility. Only those infertile ladies whose husbands showed normal semen analysis are included in the study. A detailed clinical history, marital, obstetric history, coital history, addiction history of the patients is taken. Thorough gynaecological examination is done and all necessary investigations is done. All infertile women and women willing to participate are included in the study. Women with male factor infertility and active genital infections are excluded. Results: Out of 50 infertile women, 36 have primary infertility and 14 have secondary infertility. Of them 24 (48%) have normal findings. Ten (20%) women have unilateral tubal blockage, 4 (8%) women had bilateral tubal blockage, 8 (16%) women have adhesions between ovaries, tubes, uterus and surrounding structures and 4 (8%) women have polycystic ovaries. Conclusions: Hystero laparoscopy proved to be an important tool in diagnosing the different causes of female infertility.